Connection effect on amplitude death stability of multi-module floating airport. (1st January 2017) - Zhang, H.C.; Xu, D.L.; Lu, C.; Qi, E.R.; Tian, C.; Wu, Y.S.
Abstract: A floating airport consists of multiple floating modules that are serially connected by flexible connectors. A generalized 2D dynamic network model is developed for its dynamic analysis with mooring constraints. Three connection models, including the parallel hinge type, cross hinge type and compound type, are proposed for assessing the performance of dynamic stability in terms of amplitude death that leads to a weak oscillation state. Numerical results illustrate the onset of amplitude death stability of the three models in the parameters domain spanned by the connector stiffness and wave period, in addition with the effect of wave height. The comparison study concludes that the compound type connection may deliver better dynamic stability, which can significantly improve the safety design of multi-module floating airport. Highlights: Floating airport coupled with flexible connectors can be viewed as a dynamic network. The special dynamic behavior of amplitude death (weak oscillatory state) is studied. Three connection models are proposed for assessing the performance of dynamic stability. The work presents an application example to improve the connector design of the VLFS.